2016
DOI: 10.1016/j.jhazmat.2016.07.045
|View full text |Cite
|
Sign up to set email alerts
|

Non-equilibrium passive sampling of hydrophobic organic contaminants in sediment pore-water: PCB exchange kinetics

Abstract: This study investigates the isotropic exchange kinetics of PCBs for polyethylene (PE) passive samplers in quiescent sediment and develops a novel non-equilibrium passive sampling method using PE with multiple thicknesses. The release and uptake kinetics of PCBs in quiescent sediment are reproduced by a 1-D diffusion model using sediment diffusion parameters fitted with the data from actual measurements. From the sediment diffusion parameters observed for uptake and release kinetics, it is seen that the uptake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…For instance, Rochman et al (2013) reported that LDPE required at least 6 months to reach sorption equilibrium of PCBs or polycyclic aromatic hydrocarbons (PAHs) in San Diego Bay under field conditions . Choi et al (2016) observed only 11% of the preloaded PCB192 desorbed from 102 μm PE after 264 d of deployment in sediment . Therefore, given that the clean or precontaminated microplastics were deployed in the soil for only 28 d in this study, it was unlikely that the sorption in the S1 scenario and the desorption in the S2 scenario can reach phase equilibrium.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…For instance, Rochman et al (2013) reported that LDPE required at least 6 months to reach sorption equilibrium of PCBs or polycyclic aromatic hydrocarbons (PAHs) in San Diego Bay under field conditions . Choi et al (2016) observed only 11% of the preloaded PCB192 desorbed from 102 μm PE after 264 d of deployment in sediment . Therefore, given that the clean or precontaminated microplastics were deployed in the soil for only 28 d in this study, it was unlikely that the sorption in the S1 scenario and the desorption in the S2 scenario can reach phase equilibrium.…”
Section: Resultsmentioning
confidence: 77%
“…40 Choi et al ( 2016) observed only 11% of the preloaded PCB192 desorbed from 102 μm PE after 264 d of deployment in sediment. 41 Therefore, given that the clean or precontaminated microplastics were deployed in the soil for only 28 d in this study, it was unlikely that the sorption in the S1 scenario and the desorption in the S2 scenario can reach phase equilibrium. For the S1 scenario, PCBs on microplastics may be in the state of "underequilibrium", suggesting that PCBs in soil porewater or earthworm gut fluid preferred to sorb on microplastics, thus leading to lower accumulation.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…For example, for the strongly hydrophobic DDT compounds, equilibrium was not achieved for a 51 μm PE film even after one year under field conditions. 36 Choi et al (2016) reported that only 20% of PCB192 preloaded onto a 17 μm PE film was desorbed after 265 d in a sediment. 51 Several studies further showed slow mass transfer from microplastics to the surrounding environments under static conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…36 Choi et al (2016) reported that only 20% of PCB192 preloaded onto a 17 μm PE film was desorbed after 265 d in a sediment. 51 Several studies further showed slow mass transfer from microplastics to the surrounding environments under static conditions. For instance, Endo et al (2013) evaluated desorption of PCBs from field-collected PE pellets via long-term desorption and diffusion modeling, and estimated that the time to reach equilibrium spanned from 2.8 yr for PCB8 and up to 3500 yr for PCB209 under near static conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The C free estimated using CPEt and PRC results can then be compared to measured CPE or CPE extrapolated from the uptake curve. Recent temporal studies using PRC‐loaded passive samplers in quiescent sediments showed mixed results and indicate caution in the use of PRCs in field applications (Bao et al 2016; Choi et al 2016). To the best of our knowledge, this type of study has not been conducted in surface waters, where the sampling kinetics are more easily modeled.…”
Section: Introductionmentioning
confidence: 99%